2014
DOI: 10.3747/co.21.2069
|View full text |Cite
|
Sign up to set email alerts
|

The Trastuzumab and Vinorelbine Combination: An Alternative to Taxane-Based Chemotherapy for Early-Stage and Locally Advanced HER2-Positive Breast Cancer

Abstract: ConclusionsFor patients with non-metastatic breast cancer refusing alopecia, or for patients who are not candidates for standard chemotherapy, tv is a reasonable alternative to standard adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…In this retrospective study, we found that TV in the adjuvant setting had encouraging efficacy, but a milder toxicity profile (no long-term neuropathy or alopecia). Our results are consistent with other studies supporting a favorable toxicity profile and clinical activity of the TV regimen in treatment of metastatic 11,12 and early-stage 14,15 HER2+ BC. Our work supports the findings from important earlier works that evaluated the TV regimen in early HER2-positive BC 14,15 with the advantage of longer follow-up, and data from a more recent follow-up period, reflecting contemporary clinical guidelines for that patient population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this retrospective study, we found that TV in the adjuvant setting had encouraging efficacy, but a milder toxicity profile (no long-term neuropathy or alopecia). Our results are consistent with other studies supporting a favorable toxicity profile and clinical activity of the TV regimen in treatment of metastatic 11,12 and early-stage 14,15 HER2+ BC. Our work supports the findings from important earlier works that evaluated the TV regimen in early HER2-positive BC 14,15 with the advantage of longer follow-up, and data from a more recent follow-up period, reflecting contemporary clinical guidelines for that patient population.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies supporting a favorable toxicity profile and clinical activity of the TV regimen in treatment of metastatic 11,12 and early-stage 14,15 HER2+ BC. Our work supports the findings from important earlier works that evaluated the TV regimen in early HER2-positive BC 14,15 with the advantage of longer follow-up, and data from a more recent follow-up period, reflecting contemporary clinical guidelines for that patient population. In addition, our work included a more uniform cohort of low-risk early HER2+ patients who received the TV regimen in the adjuvant treatment instead of the accepted TH regimen, unlike other studies which included patients in the neoadjuvant setting that were likely higher-risk patients who would have received a more aggressive regimen according to current guidelines, if treated today.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At present, in addition to capecitabine, no relevant reports have been observed to evaluate the specific efficacy of pyrotinib combined with other chemotherapeutic drugs. According to the experience of trastuzumab, tegafur [19], paclitaxel [20], vinorelbine [21] and cemcitabinecan [22] also be selected for combination chemotherapy. Therefore, when we developed the combination chemotherapy regimen, we selected other drugs for patients who had previously used capecitabine and also achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of the Phase I combination study in 2011, the preferred first-line chemotherapy regimens recommended by the National Comprehensive Cancer Network (NCCN) [ 3 ]—which combined TRA with one and/or two anticancer drugs, e.g., PTX [ 4 , 5 ], DTX [ 6 10 ], capecitabine [CAPE] [ 7 , 11 , 12 ], and vinorelbine [VNR] [ 10 , 13 , 14 ]—were conducted for patients with HER2-positive recurrent or metastatic breast cancer. The package inserts of these anticancer drugs describe the following as major AEs: (1) TRA: cardiomyopathy and anaphylactoid symptoms; (2) PTX: myelosuppression, hypersensitive reaction, and peripheral neuropathy; (3) DTX: myelosuppression, anaphylaxis, and nail disorders; (4) CAPE: dehydration, hand-foot syndrome, and hepatopathy; and (5) VNR: myelosuppression, interstitial pneumonia, pulmonary congestion, and phlebitis.…”
Section: Discussionmentioning
confidence: 99%